Assessment of autochthonous lactic acid bacteria as starter culture for improving traditional Chinese Dongbei Suancai fermentation. (15th March 2023) - Zhao, Yujuan; Zhao, Zijian; Gao, Yansong; Yang, Ge; Liu, Xiaoxiao; Huang, Ruochen; Liang, Wei; Li, Shengyu
Abstract: Vegetables which provide many nutrients are an essential part of human diet. Since raw vegetables usually stay fresh for a short time and rot quickly, microbial fermentation has been used to extend the shelf-life of fresh vegetables, such as pickled cucumbers and beets. In this study, Lactiplantibacillus plantarum DP189 and Leuconostoc mesenterides subsp. mesenteris UA107 were introduced as starter cultures in the fermentation process of Dongbei Suancai, which is a popular traditional fermented vegetables in northeast China. The results showed that the LAB starter inoculation increased the diversity of flora, and Lactiplantibacillus remained the dominant flora in the middle and late fermentation stages. Meanwhile, Dongbei Suancai inoculated with the lactic acid bacteria (LAB) starter produced acid more rapidly, accompanied by better utilization of soluble protein and reducing sugar, increased contents of lactic acid and umami amino acids, and the total amount of volatile flavor substances increased by 12.43 % compared with the control group. Spearman's rank correlation analysis showed that Lactiplantibacillus, Leuconostoc mesenteroides, Acinetobacter, and Pedobacter were closely correlated with physicochemical characteristics and flavor metabolites. In conclusion, inoculating autochthonous LAB starter affected the fermentation through microbial community and metabolic regulation, and improved the quality of Dongbei Suancai. Graphical abstract: Image 1 Highlights: The starter improved the physicochemical characteristics and quality of Suancai. Lactobacillus predominated the later stage of the Suancai fermentation. 6 organic acids, 17 amino acids and 65 volatile flavours were detected in Suancai. A correlation among microbiota and metabolites in Suancai was revealed.